Safety of intravenous iron use in chronic kidney disease. Issue 6 (November 2016) - Kalra, Philip A.; Bhandari, Sunil
Abstract : Purpose of review: Iron deficiency anaemia (IDA) is common and associated with fatigue, reduced quality of life and poorer clinical outcomes. Treatment with oral iron is often inadequate and international guidelines recommend intravenous (i.v.) iron as the preferred option for the treatment of IDA in certain clinical situations. In this review, we assess the safety of using i.v. iron with a particular focus on patients with chronic kidney disease. Recent findings: Recent publications have raised safety concerns regarding the incidence of serious reactions accompanying i.v. infusion, as well as the subsequent risk of infections and cardiovascular events. Methodological flaws influence the interpretation of these data that lack evidence from the use of modern irons. The latter have been investigated in several randomized control trials. Summary: There is a need for better understanding and definition of the nature of i.v. iron reactions, as many are nonserious infusion reactions rather than true anaphylaxis. Retrospective identification of anaphylaxis is difficult and we suggest the importance of reanalysing data using fatalities or standardized terms as outcome measures. With the exception of high molecular weight iron dextran, serious or life-threatening reactions are rare with the use of i.v. irons, and they can be used safely for the treatment of IDA.